Peran E-Business dalam Optimalisasi Digital Marketing untuk Peningkatan Penjualan di E-Commerce - merlyn, merlyn anggraini; Muhammad Ikbal Fasa (LPPM STIE Mujahidin Tolitoli, 2025)
This research discusses the role of e-business in optimizing digital marketing to increase sales in e-commerce. The development of information technology has pushed digital transformation that allows businesses to reach a wider market through effective digital marketing strategies. This study uses a qualitative method with a literature approach to analyze how e-business contributes to increasing the effectiveness of digital marketing. Research results show that digital marketing integrated with e-business is able to increase customer interaction, operational efficiency, and sales conversion. The main factors that affect the success of this strategy include the use of social media, big data, artificial intelligence (AI), and omnichannel approach. Therefore, the optimal implementation of e-business is very important for companies in facing the increasingly tough e-commerce competition.